Generasi Z dan Situs Judi Online: Studi Kasus Ketergantungan Media dalam Perilaku Judi Online Slot di Kalangan Mahasiswa UNS - Jagat Afghani Gangsar Sutrisna; Prahastiwi Utari (Universitas Sebelas Maret (UNS), 2026)
This study examines online gambling addiction among university students, focusing on the prevalence of online gambling sites among Generation Z. The background of this research is based on the negative impact of online gambling behavior on students’ real lives, which not only disrupts social norms but also affects their psychological well-being. To analyze this phenomenon, the study applies the Media Dependency Theory by Sandra Ball-Rokeach and Melvin DeFleur. This theory is used to understand how media influences perception, shapes thinking patterns, and fosters individual dependence on online gambling sites. This study employs a qualitative method with a phenomenological approach to identify the characteristics of online gambling sites, including various slot games offered and aggressive promotional strategies conducted by promoters or